POLSKA HISTORIOGRAFIA XIX WIEKU WOBEC ZAGADNIENIA „KLĘSKI POGRUNWALDZKIEJ” - Renata Knyspel-Kopeć (In Gremium. Studies in History, Culture and Politics, 2019)
The most important event of the Polish-Lithuanian-Teutonic War was the battle of Grunwald. Thevictorious army, led by Władysław Jagiełło, was thus presented with an opportunity to try and finish offthe Teutonic Knights. The king with his army then laid siege to the capital of the Order, Marienburg(Malbork). They failed, however, to take the stronghold, so the Grunwald victory, spectacular though itwas, did not result in achieving the main objective of the war, i.e. the liquidation of the monastic stateof the Teutonic Knights. The Polish 9th-century historians with one voice comment on that failure ofthe Polish-Lithuanian army: while Grunwald’s victory showed Poland’s power, not taking the enemy’scapital meant defeat. The commanders of the joint armies are blamed with sluggishness that wasted anopportunity for an easy capture of the castle which got strongly fortified by grand master Heinrich vonPlauen. Yet, the 9th-century historiographers show understanding of the ‘Marienburg failure’ – seeing itssource in the food shortages and lack of experience in handling the siege on the part of the joint armies.One ought to remember, however, that the historians’ biased, negative opinion on king Władysław Jagiełłofollowed Jan Długosz’s Chronicle’s unfavourable account of the king – then the main source text.